Impact of a novel protein meal on the gastrointestinal microbiota and the host transcriptome of larval zebrafish Danio rerio - Rurangwa, Eugene; Sipkema, Detmer; Kals, Jeroen; ter Veld, Menno; Forlenza, Maria; Bacanu, Gianina M.; Smidt, Hauke; Palstra, Arjan P. (Frontiers in Physiology, 2015)
Larval zebrafish was subjected to a methodological exploration of the gastrointestinal microbiota and transcriptome. Assessed was the impact of two dietary inclusion levels of a novel protein meal (NPM) of animal origin (ragworm Nereis virens) on the gastrointestinal tract (GIT). Microbial development was assessed over the first 21 days post egg fertilisation (dpf) through 16S rRNA gene-based microbial composition profiling by pyrosequencing. Differentially expressed genes in the GIT were demonstrated at 21 dpf by whole transcriptome sequencing (mRNAseq). Larval zebrafish showed rapid temporal changes in microbial colonization but domination occurred by one to three bacterial species generally belonging to Proteobacteria and Firmicutes. The high iron content of NPM may have led to an increased relative abundance of bacteria that were related to potential pathogens and bacteria with an increased iron metabolism. Functional classification of the 328 differentially expressed genes indicated that the GIT of larvae fed at higher NPM level was more active in transmembrane ion transport and protein synthesis. mRNAseq analysis did not reveal a major activation of genes involved in the immune response or indicating differences in iron uptake and homeostasis in zebrafish fed at the high inclusion level of NPM.